ANALISIS TINGKAT KESADARAN MASYARAKAT DALAM MEMBAYAR ZAKAT PERTANIAN - Rusyadi, Abdul Latif; Imsar, Imsar (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This study aims to investigate (1) whether farmers in Dolok Batu Nanggar Sub-district have comprehended trade zakat, (2) whether they possess the awareness to fulfill their agricultural zakat obligations, and (3) what reasons underlie the non-payment of agricultural zakat among them. Employing a qualitative approach, the research was conducted in Dolok Batu Nanggar Sub-district, Simalungun Regency. The study participants were fifteen rice farmers who met the nisab threshold for agricultural zakat. The primary focus was on understanding their awareness regarding agricultural zakat payment. Data were collected through observations, interviews, and document analysis, and analyzed through techniques including data collection, reduction, presentation, and verification. Findings revealed that while farmers in Dolok Batu Nanggar Sub-district possessed a basic understanding of agricultural zakat, they lacked comprehensive knowledge regarding its calculation, rates, and nisab. Moreover, there was a low level of awareness among these farmers regarding their agricultural zakat obligations. Of the fifteen informants, only three (20%) had paid their agricultural zakat, while the remaining twelve (80%) had not. Reasons for non-payment included insufficient understanding of agricultural zakat, prioritization of personal matters, and perception of insufficient harvest yield.